Multilingualism and its social and cultural impact in the city of Kirkuk - المدرس المساعد عبداهلل ادهم نصرالدين (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
Language is a cultural and intellectual store and a receptacle for human civilization. A person who has learned a language is not learning that language as a mere tool of understanding, but learning its culture in all its details, adhering to the values of its speakers and imbuing their patterns of thinking. Any positivity and any backwardness in language necessitates backwardness in culture because language is not an innocent means of learning; it is charge that might be invested positively and negatively. Language is not only useful for communication between individuals, but also it leads and guides the human mind. Moreover, it is a means of preserving the cultural heritage of societies, and it regulates social relations and helps to foster community collaboration. Hence, it came to the mind of the researcher to examine the multilingualism in Iraq and its impact on the social fabric. The aim is to reveal the effect of the multiplicity of these languages on the formation of social ties, thus helping members of one society to establish social and cooperative relations that positively affect the establishment of relations between the nationalities of these languages. The researcher found that he who speaks Iraqi languages in the city (Kirkuk), for example, is the most understandable and cultured member of the community in the social relations between the members of these languages. He can think, eat, drink and act like them, which increases the area of his culture, his multiplicity of ideas, his acceptance by others and his acceptance of others.